Circulating Tumor DNA in KRAS positive colorectal cancer patients as a prognostic factor – a systematic review and meta-analysis. (October 2020) - Perdyan, Adrian; Spychalski, Piotr; Kacperczyk, Justyna; Rostkowska, Olga; Kobiela, Jarek
Graphical abstract: Highlights: Liquid biopsy is an arising tool in oncology including assessment of prognosis in CRC Presence of ctDNA with KRAS mutation is associated with inferior prognosis High concentration of ctDNA with KRAS mutation is associated with inferior prognosis Subgroup of KRAS tumor and plasma positive patients is likely to have worse prognosis Establishing cut-off concentrations is warranted for further clinical implementation Abstract: Background: Liquid biopsy is a novel tool in oncology. It provides minimally invasive detection of tumor specific DNA. This review summarizes data on presence of circulating tumor DNA in serum or plasma of CRC patients as a potential negative prognostic factor. Materials and Methods: The systematic review was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The search was performed using PubMed, Web of Science and Scopus. Results: In total 18 articles with a total of 1779 patients met the inclusion criteria. Six out of 8 studies found that presence of ctDNA in plasma/serum was associated with inferior overall survival. All 6 studies found that high concentrations of ctDNA in plasma/serum was associated with inferior overall survival. Conclusions: Presence or high concentrations of KRAS mutation in plasma or serum were associated with inferior prognosis. Establishing cut-off concentrations is warranted for further clinical implementation of liquid biopsy.